Identifying the key social factors in post occupancy evaluation of a green building / Siti Nurul Ainun Mohd Mustafa ... [et.al.] - Mohd Mustafa, Siti Nurul Ainun; Khali, Natasha; Mohamad Bohari, Asmah Alia; Nguyen, Hong-Trang (Universiti Teknologi MARA Cawangan Sarawak, 2022)
Over the years, researchers have conducted various studies on the adverse effects from world development growth. The real-time evidence of changes in the climate favours the stakeholders to support the sustainable development concept by balancing the environment, economic, and social needs. The construction industry is one of the industries held responsible for the release of harmful emissions throughout its lifecycle. The awareness of the need of supporting the sustainable principle has led to many initiatives in reducing the energy consumption in buildings, which include the demand for green building construction. Although extensive research and evaluation tools of green buildings are carried out, less attention is made on social needs, which include the occupants' perception and satisfaction. Consequently, recent studies found discrepancies in occupant satisfaction claiming better comfort and health in green buildings.